How does the G20 Summit affect land market? Evidence from China - Du, Xuejun; Huang, Zhonghua (International Journal of Strategic Property Management, 2021)
We employ the difference-in-difference and synthetic control methods to investigate the capitalization effect of hosting the G20 Summit on land market, based on China’s land transaction dataset from 2011 to 2019. We find that hosting the G20 Summit has a significant positive effect on land prices in the host city, increasing land prices by over 22.6% compared to comparable cities. The impact of hosting the G20 Summit on land prices is larger in the post-G20 period than in the preparation period. Further, hosting the G20 Summit has heterogeneous and distributional effects on land prices. The capitalization effects of venue construction and transportation infrastructure upgrading on land prices are the main channels.